Revocable Identity-Based Matchmaking Encryption with Equality Test for Smart Healthcare - Xiaokun Zheng; Dong Zheng; Yinghui Zhang (Sensors)
Smart healthcare establishes a safe, reliable, and efficient medical information system for the public with the help of the Internet of Things, cloud storage, and other Internet technologies. To enable secure data sharing and case-matching functions in smart healthcare, we construct a revocable identity-based matchmaking encryption with an equality test (RIBME-ET) scheme for smart healthcare. Our scheme not only ensures the confidentiality and authenticity of messages and protects the privacy of users, but also enables a cloud server to perform equality tests on encrypted ciphertexts from different identities to determine whether they contain the same plaintext and protects the confidentiality of data in the system through a user revocation mechanism. Compared with the existing identity-based encryption with equality test (IBEET) and identity-based matchmaking encryption with equality test (IBME-ET) schemes, we have improved the efficiency of the scheme and reduced communication overhead. In addition, the scheme’s security is proven in the random oracle model under the computational bilinear Diffie–Hellman (CBDH) assumption. Finally, the feasibility and effectiveness of the proposed scheme are verified by performance analysis.